Changes of individual perception in psychosocial stressors related to German reunification in 1989/1990 and cardiovascular risk factors and cardiovascular diseases in a population-based study in East Germany - Bohley, Stefanie; Kluttig, Alexander; Werdan, Karl; Nuding, Sebastian; Greiser, Karin Halina; Kuß, Oliver; Markus, Marcello Ricardo Paulista; Schmidt, Carsten Oliver; Völzke, Henry; Krabbe, Christine; Haerting, Johannes (BMJ open, 2016)
EPIDEMIOLOGY; SOCIAL MEDICINE